Pengaruh Pemberian Formalin Peroral Terhadap Mukosa Lambung Tikus Putih Strain Wistar (Rattus Norvegicus Strain Wistar) - Romdhoni, Muhammad Fadhol (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2015)
The Effect of Oral Formalin on Gastric Mucosa of Wistar Strain White Rats (Rattus Norvegicus Wistar Strain)  Background: Gastritis represent one of more disease in clinic, on 2001 prevalention of cronic gastritis in Indonesia 4.3% of 100.000 population and caused additive like formaldehyde. Formaldehyde was misused especially in food industry, if consumed can cause organ’s disparity. Intention of this research is prove the Effect of Formaldehyde peroral subacute on the stomach mucosal of White Rat Strain Wistar (Rattus Norvegicus strain wistar)Method : The design of the study was pure experimental which usingThe Posttest Control Group Design. Sample were white mice which divided into 4 groups. Group I is as a control, without formaldehyde, and another groups were given with formaldehyde doses 20 ppm, 40 ppm, and 80 ppm.  Result: The results should that formaldehyde can cause hyperplasia, hypertrophic, atopic, chafe (ANOVA p=0.000). The mechanism of action possibility as DNA cross-linked by protein than gene expression anormal. Conclusions: The study concluded that formaldehyde can cause hyperplasia, hypertrophic, atopic, and chafe on the mucosal stomach of white rat strain wistar and further study was needed to know minimum doses than can change of stomach mucosal and than mecahanism of action about them.